Morgagni Hernia Presented With Acute Gastric Obstruction and Mediastinal Shift - Kaya, Şeyda Örs; Aytekin, Faruk; Liman, Şerife Tuba; Tekin, Koray; Yağcı, Baki (Fırat University, 2005)
Morgagni hernias, rarely seen in adults, are usually asymptomatic, but they may cause some severe complications. A case of Morgagni hernia with acute gastrointestinal obstruction and respiratory distress due to sudden mediastinal shift was presented here.

Morgagni hernileri yetişkinlerde nadiren görülmekte olup, genellikle asemptomatiktir. Ancak bazı ciddi komplikasyonlara neden olabilirler. Gastrointestinal obstrüksiyon ve ani gelişen mediastinal şift nedeniyle solunum distresli bir Morgagni Hernisini burada sunuyoruz.
Akut Gastrik Obstrüksiyon ve Mediastinal Şiftle Birlikte Morgagni Hernisi